2018
DOI: 10.14814/phy2.13577
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive immune responses are altered in adult mice following neonatal hyperoxia

Abstract: Premature infants with bronchopulmonary dysplasia (BPD), are at risk for frequent respiratory infections and reduced pulmonary function. We studied whether neonatal hyperoxia disrupts adaptive immune responses in adult mice, contributing to higher respiratory‐related morbidities seen in these infants. Newborn mice litters were randomized at 3 days to 85% O2 or room air (RA) for 12 days. Whole lung mRNA was isolated in both the groups at 2 weeks and 3 months. Gene expression for T‐cell and B‐cell adaptive immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Many patients would have received oxygen, and it is interesting to consider the potential effects of this therapy on clock-regulated pathways and disease outcomes. Importantly, several reports show that supplemental oxygen given to premature infants associates with a risk of lung dysfunction and susceptibility to respiratory infections in adult life ( Buczynski et al, 2013 ; Yee et al, 2013 ; Kumar et al, 2018 ).…”
Section: Host Immune Responses and Covid-19 Pathologymentioning
confidence: 99%
“…Many patients would have received oxygen, and it is interesting to consider the potential effects of this therapy on clock-regulated pathways and disease outcomes. Importantly, several reports show that supplemental oxygen given to premature infants associates with a risk of lung dysfunction and susceptibility to respiratory infections in adult life ( Buczynski et al, 2013 ; Yee et al, 2013 ; Kumar et al, 2018 ).…”
Section: Host Immune Responses and Covid-19 Pathologymentioning
confidence: 99%
“…These data speak for a protective effect of Lpar1 in oxygen-injury in rat lungs. In another study, exposure to hyperoxia in the neonatal period was documented to cause changes in adaptive cellular immunity that persisted into adulthood (286), where exposure of mouse pups to hyperoxia between P3 and P12 impacted both T cell and B cell activation, which was noted during hyperoxia exposure, as well as in adult mice after a 10-week recovery after hyperoxia exposure. No studies on lung structure were undertaken in that study, and the association between alterations to T cell and B cell activation and lung alveolarization remains cor-…”
Section: Inflammationmentioning
confidence: 98%
“…In a baboon BPD model, investigations into thymic involution provided evidence that thymic architecture and T cell function are altered leading to autoreactivity and immunodeficiency (11). Further mouse studies of neonatal hyperoxia-induced lung injury demonstrated a dysregulation of thymopoiesis and altered adaptive immune responses which persisted into adulthood (12,13). These data suggest that hyperoxia-induced thymic atrophy during the neonatal period results in long-term complications with an autoimmune component.…”
Section: Introductionmentioning
confidence: 95%
“…The camera shutter speed was fixed at 30.1 ms and camera gain to 500. The camera sensitivity and detection threshold were set for (11)(12)(13)(14) and (4)(5)(6), respectively. For each sample, three videos of 60 seconds were recorded using the NTA software (version 3.0), and individual samples were run in triplicate.…”
Section: Characterization Of Wj-msc Derived Evsmentioning
confidence: 99%